2014
DOI: 10.1111/bjp.12074
|View full text |Cite
|
Sign up to set email alerts
|

Psychoanalytic Psychotherapy in Contemporary Mental Health Services: Current Evidence, Future Role and Challenges

Abstract: Three interacting challenges are facing all aspects of health care in the United Kingdom: financial restraint in the context of a global economic downturn; a move to services being commissioned and decommissioned by primary care Clinical Commissioning Groups; and a need to provide evidence based practice through 'payment by results'. Psychoanalytic psychotherapy faces more difficulty than most services in mental health, with long and frequent criticisms of it being expensive and underresearched; and it is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…This must be further filtered through the reality of a mandated £20 billion in efficiency savings in the National Health Service (NHS) by 2014, 8 creating competition for ever-reduced resources. 9 There are specific dangers for rehabilitation services in this context: a lack of clear governmental policy support and a limited – though generally positive – scientific evidence base could result in a loss of money to competing services. Commissioners' knowledge of the role and effectiveness of rehabilitation is uncertain, although specific guidance to assist commissioning has been produced.…”
mentioning
confidence: 99%
“…This must be further filtered through the reality of a mandated £20 billion in efficiency savings in the National Health Service (NHS) by 2014, 8 creating competition for ever-reduced resources. 9 There are specific dangers for rehabilitation services in this context: a lack of clear governmental policy support and a limited – though generally positive – scientific evidence base could result in a loss of money to competing services. Commissioners' knowledge of the role and effectiveness of rehabilitation is uncertain, although specific guidance to assist commissioning has been produced.…”
mentioning
confidence: 99%
“…Therefore, numerous studies have been carried out in recent years on the effectiveness of psychodynamic therapies, and the findings support the effectiveness of this therapy on mild and complex mental health problems (1). Meta-analyses show the impact of psychodynamic therapies on the symptoms of many psychiatric disorders, for example, personality disorders (17), Depression (18,19), Schizophrenia (20,21); and even in long-term psychoanalytic therapy (2,22,23).…”
Section: Discussionmentioning
confidence: 89%
“…In recent decades, considerable researches have confirmed the efficacy of psychodynamic therapies, particularly in the field of short-term psychodynamic psychotherapy (1). The interesting point is that, by reviewing the literature which have compared the results of different psychotherapies, it was revealed that the efficacy of these therapies are equal in many cases and no form of psychotherapy was superior to the others (2,3).…”
Section: Introductionmentioning
confidence: 99%